A prey‐predator model with diffusion and a supplementary resource for the prey in a two‐patch environment - Dhar, J. (Mathematical Modelling and Analysis, 2004)
In this paper, a prey‐predator dynamics, where the predator species partially depends upon the prey species, in a two patch habitat with diffusion and there is a non‐diffusing additional resource for the prey population, is modeled and analyzed. It is shown, that there exists a positive, monotonic, continuous steady state solution with continuous matching at the interface for both the species separately. Further, we obtain conditions for asymptotic stability for both linear and nonlinear cases. Plėšrūno-aukos modelis su difuzija ir papildomu resursu aukai dviejų sričių areale Santrauka. Šiame straipsnyje modeliuojama ir analizuojama plėšrūnų ir aukų dinamika, laikant, kad plėšrūnų populiacija dalinai priklauso nuo aukų skaičiaus. Arealą sudaro dvi sritys, kuriose vyksta populiacijų individų difuzija, be to, aukoms yra išskirtas nedifunduojantis resursas. Įrodyta, kad egzistuoja teigiamas, monotoniškas, tolydus stacionarusis sprendinys, tenkinantis tolydumo sąlygą abiems populiacijoms atskirai. Gautos asimptotinio stabilumo sąlygos tiesiniu ir netiesiniu atvejais. First Published Online: 14 Oct 2010